DASHBOARD INDICATORS OF THE PUBLIC SERVICE - N. Altuhova; E. Vasil¢Eva; A. Gromova; B. Slavin (Вестник университета)
It formulated the need for new guidelines that take into account the possibility of formalization and analysis of processes in the discharge of public functions by public servants. Dashboard monitoring of the execution of state functions to civil servants is one of the topics to be discussed today. However, for the possibility of monitoring the key task is to identify the key evaluation indicators. Among the dashboard indicators need to be identified such as the performance, team and leadership assessment effective organization of the processes of execution of the state functions and competences of civil servants. To analyze the data from different angles and positions, is the best data exploration tool Data Discovery.